Layered thermoelectric material with low lattice thermal conductivity and preparation method thereof

By doping indium into the GeSb4Te7-based material, a single-phase thermoelectric material of Ge1-xInxSb4Te7 (0<x≤0.1) was prepared, which solved the problem of high lattice thermal conductivity of the Ge-Sb-Te system thermoelectric material, achieved low lattice thermal conductivity, improved Seebeck coefficient and thermoelectric superiority, and provided support for its application in the fields of thermoelectric materials and thermal barrier coatings.

CN119562749APending Publication Date: 2025-03-04JIHUA LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510023463.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing Ge-Sb-Te system thermoelectric materials have high lattice thermal conductivity, which limits their application in the fields of thermoelectric materials and thermal barrier coatings.

Method used

By doping indium into the GeSb4Te7-based material, a single-phase thermoelectric material with the general formula of Ge1-xInxSb4Te7 (0

Benefits of technology

It effectively reduces the lattice thermal conductivity of GeSb4Te7 material, improves the Seebeck coefficient and thermoelectric superiority, solves the problem of generally high thermal conductivity of Ge-Sb-Te base layered materials, and provides material support for its application in the fields of thermal barrier coatings, thermoelectric devices, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562749A_ABST
    Figure CN119562749A_ABST
Patent Text Reader

Abstract

The invention discloses a layered thermoelectric material with low lattice thermal conductivity and a preparation method thereof, and relates to the technical field of thermoelectric materials, the structural formula of the thermoelectric material is Ge1-xInxSb4Te7, and x is more than 0 and less than or equal to 0.1. According to the thermoelectric material, indium is doped in a GeSb4Te7 material through a hot pressed sintering preparation process, the lattice thermal conductivity of the GeSb4Te7 material can be effectively reduced, the Seebeck coefficient and the thermoelectric figure of merit of the GeSb4Te7 material can be improved, the problem that the lattice thermal conductivity of a Ge-Sb-Te-based layered material is generally high is solved, and material support is provided for application of the Ge-Sb-Te-based material in the fields of thermal barrier coatings, thermoelectric devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermoelectric materials, and in particular to a layered thermoelectric material with low lattice thermal conductivity and a preparation method thereof. Background Art

[0002] Thermoelectric materials are functional materials that can realize the direct conversion between thermal energy and electrical energy. As key materials for new energy technologies, thermoelectric materials have broad application prospects and huge potential. They are widely used in many fields such as waste heat collection, semiconductor chip cooling, refrigeration, infrared detection, etc. The large-scale application of thermoelectric materials is mainly limited by their low energy conversion efficiency. Therefore, improving the thermoelectric performance of materials remains the focus of current research. The excellent thermoelectric conversion efficiency of materials can be characterized by the thermoelectric figure of merit (zT): the larger the thermoelectric figure of merit, the higher the thermoelectric conversion efficiency. The thermoelectric figure of merit is defined as

[0003] Among them, S, <, T, and k represent Seebeck coefficient, electrical conductivity, absolute temperature, and thermal conductivity (lattice thermal conductivity k L and carrier thermal conductivity k e To achieve a high thermoelectric figure of merit zT, it is necessary to simultaneously achieve high electrical conductivity, high Seebeck coefficient and low thermal conductivity of the material. However, due to the mutual coupling of electrical and thermal transport parameters, especially the strong coupling relationship between carrier transport and phonon transport, it is difficult to optimize them simultaneously to improve the thermoelectric figure of merit.

[0004] In the prior art, the Ge-Sb-Te system is a hot topic in the research of thermoelectric materials. Among them, Ge-Sb-Te ternary compounds with layered structures (such as GeSb2Te4, Ge2Sb2Te5 and GeSb4Te7) are quasi-two-dimensional p-type semiconductor materials with narrow band gap, high conductivity and low thermal conductivity, and are considered to be promising layered thermoelectric materials. However, the lattice thermal conductivity of Ge-Sb-Te-based layered materials is relatively high, which limits their application in fields related to thermal energy conversion and management, such as thermoelectric materials and thermal barrier coatings.

[0005] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a layered thermoelectric material and a preparation method thereof, aiming to solve the defect of high lattice thermal conductivity of thermoelectric materials of the Ge-Sb-Te system in the prior art.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A layered thermoelectric material with low lattice thermal conductivity, wherein the structural formula of the thermoelectric material is Ge 1-x In x For Sb4Te7, x is 0<x≤0.1.

[0009] In the layered thermoelectric material with low lattice thermal conductivity, x is 0.05, and the structural formula of the thermoelectric material is Ge 0.95 In 0.05 Sb4Te7.

[0010] A method for preparing a thermoelectric material, for preparing the above-mentioned layered thermoelectric material with low lattice thermal conductivity, the method comprising the steps of:

[0011] Step S1, vacuum-packing germanium powder, indium powder, antimony powder and tellurium powder in a quartz tube, heating from room temperature to 950° C., and keeping the temperature at 950° C. for 12<2 hours. After the insulation is completed, quenching the quartz tube;

[0012] Step S2, heating the quartz tube from room temperature to 590°C < 5°C at a heating rate of 2-5°C / min, and keeping it at this temperature for 40-55h, and then naturally cooling it to room temperature;

[0013] Step S3, grinding and sieving the material obtained in step S2, and then hot pressing and sintering it into a dense block. The hot pressing and sintering temperature is 420° C., the insulation time is 30 min, and the pressure is 50 MPa. After the sintering is completed, a thermoelectric material is obtained.

[0014] In the method for preparing the thermoelectric material, in step S1, the purity of the germanium powder, indium powder, antimony powder and tellurium powder is 99.99%.

[0015] In the method for preparing the thermoelectric material, the heating rates in step S1 and step S2 are both 2-5° C. / min.

[0016] In the method for preparing the thermoelectric material, in step S3, the mesh size of the ground and sieved material is 100 meshes.

[0017] In the method for preparing the thermoelectric material, in step S3, the density of the prepared single-phase thermoelectric material is 6.40-6.44 g / cm 3 .

[0018] Beneficial effects:

[0019] The first aspect of the present invention provides a layered thermoelectric material with low lattice thermal conductivity. The thermoelectric material is doped with In on the basis of GeSb4Te7 to obtain a general formula of Ge 1-x In xThe single-phase thermoelectric material of Sb4Te7 (0<x≤0.1) can effectively reduce the lattice thermal conductivity of GeSb4Te7 material, improve its Seebeck coefficient and thermoelectric figure of merit, and solve the problem of the generally high lattice thermal conductivity of Ge-Sb-Te based materials, providing material support for the application of Ge-Sb-Te based materials in thermal barrier coatings, thermoelectric devices and other fields.

[0020] The second aspect of the present invention also provides a method for preparing a thermoelectric material. The method successfully synthesizes a thermoelectric material having a general formula of Ge by melting, quenching, annealing and hot pressing sintering processes. 1-x In x Sb4Te7 (x = 0, 0.025, 0.05, 0.1) compounds. In the preparation process, the impurities can be eliminated by high-temperature melting, quenching and annealing to obtain a single-phase material; at the same time, hot pressing and sintering are used to improve the density of the single-phase material to 6.40-6.44 g / cm 3 , thus making the material have better thermoelectric properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Preparation of Ge by hot pressing 1-x In x XRD patterns of powder samples of Sb4Te7 (x=0, 0.025, 0.05, 0.1) compounds.

[0022] Figure 2 Preparation of Ge by hot pressing 1-x In x Electrical conductivity of Sb4Te7 (x=0, 0.025, 0.05, 0.1) compounds.

[0023] Figure 3 Preparation of Ge by hot pressing 1-x In x Seebeck coefficient of Sb4Te7 (x=0, 0.025, 0.05, 0.1) compounds.

[0024] Figure 4 Preparation of Ge by hot pressing 1-x In x Total thermal conductivity of Sb4Te7 (x=0, 0.025, 0.05, 0.1) compounds.

[0025] Figure 5 Preparation of Ge by hot pressing 1-x In x Lattice thermal conductivity of Sb4Te7 (x=0, 0.025, 0.05, 0.1) compounds.

[0026] Figure 6 Preparation of Ge by hot pressing1-x In x Thermoelectric figures of merit of Sb4Te7 (x=0, 0.025, 0.05, 0.1) compounds.

[0027] Figure 7 Ge prepared by hot pressing and not hot pressing 1-x In x Lattice thermal conductivity of Sb4Te7 (x=0.05) compound.

[0028] Figure 8 To prepare Ge by slow cooling 1-x In x XRD pattern of powder sample of Sb4Te7 (x=0.05) compound.

[0029] Fig. 9 For Ge 1-x In x XRD pattern of powder sample of Sb4Te7 (x=0.125) compound. DETAILED DESCRIPTION

[0030] The present invention provides a layered thermoelectric material with low lattice thermal conductivity and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0031] The first aspect of the present invention provides a layered thermoelectric material with low lattice thermal conductivity. The general formula of the thermoelectric material is Ge 1-x In x Sb4Te7, where x is 0<x≤0.1. This thermoelectric material can effectively reduce the lattice thermal conductivity of the material, improve the Seebeck coefficient and thermoelectric figure of merit of the material by doping indium in the GeSb4Te7 substrate, solving the problem of the generally high lattice thermal conductivity of Ge-Sb-Te based materials, and providing material support for the application of Ge-Sb-Te based materials in thermal barrier coatings, thermoelectric devices and other fields.

[0032] As a preferred embodiment, when x is 0.05, the structural formula of the thermoelectric material is Ge 0.95 In 0.05 Sb4Te7, a thermoelectric material of this structure, has a lattice thermal conductivity as low as 0.038 W m -1 K -1 , providing strong support for the development and application of low lattice thermal conductivity materials.

[0033] A second aspect of the present invention provides a method for preparing a thermoelectric material, the method being used to prepare the thermoelectric material as described above, the method comprising the steps of:

[0034] Step S1, vacuum-packing germanium powder, indium powder, antimony powder and tellurium powder in a quartz tube, heating from room temperature to 950° C., and keeping the temperature at 950° C. for 12<2 hours. After the insulation is completed, quenching the quartz tube;

[0035] Step S2, raising the temperature of the quartz tube from room temperature to 590°C < 5°C, keeping it at this temperature for 40 to 55 hours, and then naturally cooling it to room temperature;

[0036] Step S3, grinding and sieving the material obtained in step S2, and then hot pressing and sintering it into a dense block. The hot pressing and sintering temperature is 420° C., the insulation time is 30 min, and the pressure is 50 MPa. After the sintering is completed, a thermoelectric material is obtained.

[0037] The preparation method successfully synthesized Ge through melting, quenching, annealing and hot pressing sintering processes. 1- x In x Sb4Te7 (x = 0, 0.025, 0.05, 0.1) compounds. Wherein, in step S1, the impurity phase formed during the cooling process can be eliminated by high-temperature melting + quenching. In the melting process, setting the melting temperature to more than 900 ° C can effectively avoid the introduction of impurity phases (such as In2Te3 or Sb2Te3 phases); through step S2, the material is subjected to composition homogenization treatment in its formation temperature range to obtain a single-phase material; through step S3, hot pressing sintering is used to improve the density of the material, so that the density of the material is as high as 6.34-6.44g / cm 3 , thus making the material have better thermoelectric performance. The thermoelectric material prepared by this method has lower lattice thermal conductivity (the lowest lattice thermal conductivity is only 0.038W m -1 K -1 ), providing strong support for the development and application of low lattice thermal conductivity materials.

[0038] In a preferred embodiment, in the step S1, the purity of the germanium powder, indium powder, antimony powder and tellurium powder is 99.99%, which can avoid the formation of impurity phase and obtain a single-phase material.

[0039] In step S1 and step S2, the heating rate will affect the formation of the single-phase material. When the heating rate is too fast, it is not conducive to the chemical reaction and will also cause the material to be uneven, so that the single-phase material cannot be obtained, which in turn affects the performance; and too slow a heating rate will affect the efficiency. In this regard, in a preferred embodiment, the heating rates in step S1 and step S2 are both 2-5°C / min, which can promote the formation of the single-phase material.

[0040] In step S3, since the bulk of large particles will affect the uniformity of the material and the density of the material after hot pressing and sintering, in step S3, after grinding, the bulk of large particles is removed by sieving. The mesh number of the grinding and sieving is 100 mesh, which can obtain a more uniform particle size so that the structure is uniform after hot pressing.

[0041] To further illustrate a thermoelectric material and a preparation method thereof provided by the present invention, the following examples are provided.

[0042] Example 1

[0043] Ge 1-x In x Material preparation and performance analysis of Sb4Te7 (x=0.025)

[0044] (1) Ingredients and packaging

[0045] Using germanium powder, indium powder, antimony powder and tellurium powder with a purity of 99.99% as raw materials, germanium powder, indium powder, antimony powder and tellurium powder with a molar ratio of 0.975:0.025:4:7 are evenly mixed and placed in a quartz tube, and evacuated to ≤1Pa, and then the quartz tube containing the sample is sealed using a flame sealing device.

[0046] (2) Melting and quenching

[0047] Place the vacuum-sealed quartz tube vertically in a pit furnace, close to the thermocouple. Raise the temperature from room temperature to 950°C at a rate of 2°C / min. Keep at this temperature for 14 hours, then take out the quartz tube and quench it in water.

[0048] (3) Material annealing

[0049] For the material subjected to heat preservation and firing in step (2), the temperature was raised from room temperature to 590°C at a heating rate of 2°C / min and kept at 590°C for 48 hours; after the vacuum-sealed quartz tube was naturally cooled to room temperature, the material was taken out of the quartz tube.

[0050] (4) Material hot pressing sintering

[0051] The ingot obtained in step 3 was ground and sieved (100 mesh) and then sintered into a dense block using a rapid hot pressing sintering furnace. The hot pressing sintering temperature of the sample was 420°C, the holding time was 30 minutes, and the uniaxial pressure was maintained at 50 MPa during the holding process. The density of the material was 6.439 g / cm 3 .

[0052] (5) Material structure and performance analysis

[0053] The prepared material was characterized by X-ray diffractometer. By comparing the powder X-ray diffraction pattern of the crystal with the diffraction peaks listed in PDF#89-2232, it was determined that Ge 1-x In x Sb4Te7 (x = 0.025) to obtain a single-phase material ( Figure 1 ). Using Seebeck coefficient-conductivity tester, laser thermal conductivity meter and other equipment to test performance, it was found that the highest conductivity of this sample is at 300K, and its value is: 3.005<10 5 S m -1 ( Figure 2 ); The maximum Seebeck coefficient is at 750K, which is: 104.4μV K -1 ( Figure 3 ); the lowest thermal conductivity is at 650K, and its value is: 1.908W m -1 K -1 ( Figure 4 ); the minimum lattice thermal conductivity is at 500K, and its value is: 0.222W m -1 K -1 ( Figure 5 ); the highest thermoelectric figure of merit is at 750K, and its value is: 0.404( Figure 6 ).

[0054] Example 2

[0055] Ge 1-x In x Material preparation and performance analysis of Sb4Te7 (x=0.05)

[0056] (1) Ingredients and packaging

[0057] Using germanium powder, indium powder, antimony powder and tellurium powder with a purity of 99.99% as raw materials, germanium powder, indium powder, antimony powder and tellurium powder with a molar ratio of 0.95:0.05:4:7 are evenly mixed and placed in a quartz tube, and evacuated to ≤1Pa, and then the quartz tube containing the sample is sealed using a flame sealing device.

[0058] (2) Melting and quenching

[0059] Place the vacuum-sealed quartz tube vertically in a pit furnace, close to the thermocouple. Raise the temperature from room temperature to 950°C at a rate of 2°C / min. Keep at this temperature for 12 hours, then take out the quartz tube and quench it in water.

[0060] (3) Material annealing

[0061] For the material subjected to heat preservation and firing in step (2), the temperature was raised from room temperature to 590°C at a heating rate of 2°C / min and kept at 590°C for 48 hours; after the vacuum-sealed quartz tube was naturally cooled to room temperature, the material was taken out of the quartz tube.

[0062] (4) Material hot pressing sintering

[0063] The ingot obtained in (3) was ground and sieved (100 mesh) and then sintered into a dense block using a rapid hot pressing sintering furnace. The hot pressing sintering temperature of the sample was 420°C, the holding time was 30 minutes, and the uniaxial pressure was maintained at 50 MPa during the holding process. The density of the material was 6.400 g / cm 3 .

[0064] (5) Material structure and performance analysis

[0065] The prepared material was characterized by X-ray diffractometer. By comparing the powder X-ray diffraction pattern of the crystal with the diffraction peaks listed in PDF#89-2232, it was determined that Ge 1-x In x Sb4Te7(x=0.05) obtains single-phase material ( Figure 1 ). Using Seebeck coefficient-conductivity tester, laser thermal conductivity meter and other equipment to test performance, it was found that the highest conductivity of this sample is at 300K, and its value is: 25.08<10 4 S m -1 ( Figure 2 ); The maximum Seebeck coefficient is at 750K, which is: 118.80μV K -1 ( Figure 3 ); the lowest thermal conductivity is at 650K, and its value is: 1.51W m -1 K -1 ( Figure 4 ); the minimum lattice thermal conductivity is at 400K, and its value is: 0.038W m -1 K -1 ( Figure 5 ); the highest thermoelectric figure of merit is at 750K, which is: 0.55( Figure 6 ).

[0066] Example 3

[0067] Ge 1-x In x Material preparation and performance analysis of Sb4Te7 (x=0.1)

[0068] (1) Ingredients and packaging

[0069] Using germanium powder, indium powder, antimony powder and tellurium powder with a purity of 99.99% as raw materials, germanium powder, indium powder, antimony powder and tellurium powder with a molar ratio of 0.9:0.1:4:7 are evenly mixed and placed in a quartz tube, and evacuated to ≤1Pa, and then the quartz tube containing the sample is sealed using a flame sealing device.

[0070] (2) Melting and quenching

[0071] Place the vacuum-sealed quartz tube vertically in a pit furnace, close to the thermocouple. Raise the temperature from room temperature to 950°C at a rate of 5°C / min. Keep at this temperature for 12 hours, then take out the quartz tube and quench it in water.

[0072] (3) Material annealing

[0073] For the material sintered in step 2, the temperature is increased from room temperature to 590°C at a heating rate of 5°C / min, and kept at 590°C for 55 hours; after the vacuum-sealed quartz tube is naturally cooled to room temperature, the material is taken out of the quartz tube.

[0074] (4) Material hot pressing sintering

[0075] The ingot obtained in step 3 was ground and sieved (100 mesh) and then sintered into a dense block using a rapid hot pressing sintering furnace. The hot pressing sintering temperature of the sample was 420°C, the holding time was 30 minutes, and the uniaxial pressure was maintained at 50 MPa during the holding process. The density of the material was 6.402 g / cm 3 .

[0076] (5) Material structure and performance analysis

[0077] The prepared material was characterized by X-ray diffractometer. By comparing the powder X-ray diffraction pattern of the crystal with the diffraction peaks listed in PDF#89-2232, it was determined that Ge 1-x In x Sb4Te7(x=0.1) obtains single-phase material ( Figure 1 ). Using Seebeck coefficient-conductivity tester, laser thermal conductivity meter and other equipment to test performance, it was found that the highest conductivity of this sample was at 300K, and its value was: 18.26<10 4 S m -1 ( Figure 2 ); The maximum Seebeck coefficient is at 750K, which is: 131.50μV K -1 ( Figure 3 ); the lowest thermal conductivity is at 600K, and its value is: 1.33W m -1 K -1 ( Figure 4 ); the minimum lattice thermal conductivity is at 500K, and its value is: 0.25Wm -1K -1 ( Figure 5 ); the highest thermoelectric figure of merit is at 750K, which is: 0.61( Figure 6 ).

[0078] Comparative Example 1

[0079] Ge 1-x In x Material preparation and performance analysis of Sb4Te7(x=0)

[0080] (1) Ingredients and packaging

[0081] Using germanium powder, antimony powder and tellurium powder with a purity of 99.99% as raw materials, the germanium powder, antimony powder and tellurium powder with a molar ratio of 1:4:7 are evenly mixed and placed in a quartz tube, and the vacuum is evacuated to ≤1Pa, and then the quartz tube containing the sample is sealed using a flame sealing device.

[0082] (2) Melting and quenching

[0083] Place the vacuum-sealed quartz tube vertically in a pit furnace, close to the thermocouple. Raise the temperature from room temperature to 950°C at a rate of 2°C / min. Keep at this temperature for 12 hours, then take out the quartz tube and quench it in water.

[0084] (3) Material annealing

[0085] For the material subjected to heat preservation and firing in step (2), the temperature was raised from room temperature to 590°C at a heating rate of 2°C / min and kept at 590°C for 50 hours; after the vacuum-sealed quartz tube was naturally cooled to room temperature, the material was taken out of the quartz tube.

[0086] (4) Material hot pressing sintering

[0087] The ingot obtained in (3) was ground and sieved (100 mesh) and then sintered into a dense block using a rapid hot pressing sintering furnace. The hot pressing sintering temperature of the sample was 420°C, the holding time was 30 minutes, and the uniaxial pressure was maintained at 50 MPa during the holding process. The density of the material was 6.407 g / cm 3 .

[0088] (5) Material structure and performance analysis

[0089] The prepared materials were characterized by X-ray diffractometer. 1-x In x Sb4Te7(x=0) obtains single-phase material ( Figure 1 ). Using Seebeck coefficient-conductivity tester, laser thermal conductivity meter and other equipment, it was found that the highest conductivity of this sample was at 300K, and its value was: 31.97<10 4 S m-1 ( Figure 2 ); The maximum Seebeck coefficient is at 750K, and its value is: 106.55μVK -1 ( Figure 3 ); the lowest thermal conductivity is at 750K, and its value is: 1.97W m -1 K -1 ( Figure 4 ); the lowest lattice thermal conductivity is at 550K, and its value is: 0.41W m -1 K -1 ( Figure 5 ); the highest thermoelectric figure of merit is at 750K, which is: 0.44( Figure 6 ). Comparison of experimental data revealed that: Ge doped with indium 1-x In x Sb4Te7 (0<x≤0.1) can effectively reduce the lattice thermal conductivity of GeSb4Te7 materials, improve its Seebeck coefficient and thermoelectric figure of merit. In addition, the lattice thermal conductivity of GeSb4Te7 doped with indium is generally reduced. 1-x In x Sb4Te7 (x = 0.0.5) material has a very low lattice thermal conductivity (value of 0.038 W m -1 K -1 and 0.049W m -1 K -1 range).

[0090] Comparative Example 2

[0091] Ge 1-x In x Material preparation and performance analysis of Sb4Te7 (x=0.05)

[0092] The preparation method of this material is basically the same as that of Example 2, except that the method goes through steps (1) to (3), but does not go through step (4), and directly goes through step (5). The prepared material is characterized by an X-ray diffractometer. By comparing the powder X-ray diffraction pattern of the crystal with the diffraction peaks listed in PDF#89-2232, it is determined that the Ge 1-x In x Sb4Te7(x=0.05) obtains single-phase material ( Figure 1 ). Measurement of unsintered Ge 1-x In x The density of Sb4Te7 (x = 0.05) material is 6.31 g / cm 3 .

[0093] Performance comparison analysis shows that compared with hot pressed sintered Ge 1-x In xLattice thermal conductivity of Sb4Te7 (x = 0.05) sample, unsintered Ge 1-x In x The lattice thermal conductivity of Sb4Te7 (x = 0.05) is high. The lowest lattice thermal conductivity is at 550K, and its value is: 1.09W m -1 K -1 ( Figure 7 ). According to the experimental data, it can be determined that the cause of the un-hot pressed sintered Ge 1-x In x The reason why the lattice thermal conductivity of Sb4Te7 (x=0.05) is high is due to the low density of the sample.

[0094] Comparative Example 3

[0095] Ge 1-x In x Material preparation and structural characterization of Sb4Te7 (x=0.05)

[0096] (1) Ingredients and packaging

[0097] Using germanium powder, indium powder, antimony powder and tellurium powder with a purity of 99.99% as raw materials, germanium powder, indium powder, antimony powder and tellurium powder with a molar ratio of 0.95:0.05:4:7 are evenly mixed and placed in a quartz tube, and evacuated to ≤1Pa, and then the quartz tube containing the sample is sealed using a flame sealing device.

[0098] (2) Melting and slow cooling

[0099] Place the vacuum-sealed quartz tube vertically in a pit furnace, close to the thermocouple. Raise the temperature from room temperature to 950°C at a rate of 5°C / min, keep at this temperature for 12 hours, cool the vacuum-sealed quartz tube naturally to room temperature, and then take out the material from the quartz tube.

[0100] (3) Material hot pressing sintering

[0101] The ingot obtained in (3) was ground and sieved (100 mesh) and then sintered into a dense block using a rapid hot pressing sintering furnace. The hot pressing sintering temperature of the sample was 420°C, the holding time was 30 minutes, and the uniaxial pressure was maintained at 50 MPa during the holding process. The density of the material was 6.341 g / cm 3 .

[0102] (4) Material characterization and analysis

[0103] The prepared material was characterized by X-ray diffractometer. The main phase has the same structure as GeSb4Te7, but there is also a second phase. The arrow indicates the diffraction peak corresponding to the second phase ( Figure 8). Comparison of experimental data revealed that the impurity phase formed during the material cooling process cannot be eliminated by high temperature melting (950°C) + slow cooling.

[0104] Comparative Example 4

[0105] Ge 1-x In x Material preparation and structural characterization of Sb4Te7 (x=0.125)

[0106] (1) Ingredients and packaging

[0107] Using germanium powder, indium powder, antimony powder and tellurium powder with a purity of 99.99% as raw materials, germanium powder, indium powder, antimony powder and tellurium powder with a molar ratio of 0.875:0.125:4:7 are evenly mixed and placed in a quartz tube, and evacuated to ≤1Pa, and then the quartz tube containing the sample is sealed using a flame sealing device.

[0108] (2) Melting and quenching

[0109] Place the vacuum-sealed quartz tube vertically in a pit furnace, close to the thermocouple. Raise the temperature from room temperature to 950°C at a rate of 5°C / min. Keep at this temperature for 14 hours, then take out the quartz tube and quench it in water.

[0110] (3) Material annealing

[0111] For the material sintered in step 2, the temperature is increased from room temperature to 590°C at a heating rate of 5°C / min, and kept at 590°C for 48 hours; after the vacuum-sealed quartz tube is naturally cooled to room temperature, the material is taken out of the quartz tube.

[0112] (4) Material hot pressing sintering

[0113] The ingot obtained in (3) was ground and sieved (100 mesh) and then sintered into a dense block using a rapid hot pressing sintering furnace. The hot pressing sintering temperature of the sample was 420°C, the holding time was 30 min, and the uniaxial pressure was maintained at 50 MPa during the holding process. The density of the prepared material was 6.362 g / cm 3 .

[0114] (5) Material characterization and analysis

[0115] The prepared material was characterized by X-ray diffractometer. The main phase has the same structure as GeSb4Te7, but there is also a second phase. The arrow indicates the diffraction peak corresponding to the second phase ( Fig. 9 ). Compared with the experimental data, it is found that single-phase Ge 1-x In x The x component range of Sb4Te7 thermoelectric material is 0<x≤0.1.

[0116] In summary, through the 1-x In x The material preparation and structural analysis of Sb4Te7 (x = 0, 0.025, 0.05, 0.1, 0.125) determined that indium-doped GeSb4Te7 single phase can be obtained in the composition range of 0 < x ≤ 0.1. Among them, the highest Seebeck coefficient is in Ge 1-x In x Sb4Te7 (x = 0.1) material, at 750K, its value is: 131.50μV K -1 ; The lowest thermal conductivity is in Ge 1- x In x For Sb4Te7 (x = 0.1) material, at 500K, its value is: 0.25 W m -1 K -1 ; The lowest lattice thermal conductivity is in Ge 1-x In x For Sb4Te7 (x = 0.05) material, at 400K, its value is: 0.038 W m -1 K -1 ; The highest thermoelectric figure of merit is Ge 1-x In x Sb4Te7 (x = 0.1) material, at 750K, its value is: 0.61. By comparison, it is found that Ge doped with indium 1-x In x Sb4Te7 (0<x≤0.1) can effectively reduce the lattice thermal conductivity of GeSb4Te7 material and improve its Seebeck coefficient and thermoelectric figure of merit.

[0117] Materials with low lattice thermal conductivity are widely used in the fields of thermal barrier coatings, thermoelectric devices, etc. In the present invention, indium is doped into the GeSb4Te7 material to effectively reduce the lattice thermal conductivity of the GeSb4Te7 material. 1- x In x Sb4Te7 (x = 0.05) material has a very low lattice thermal conductivity at 400K-500K, with a value of 0.038W m -1 K -1 and 0.049W m -1 K -1 Compared with the known Ge-Sb-Te based materials lattice thermal conductivity (among which, the lowest lattice thermal conductivity of GeSb2Te4 based materials appears in GeSb2Te 3.4 Se 0.6 material, its value is 0.29W m -1 K -1(Acta Materialia, 2023, 254: 118999); The lowest lattice thermal conductivity of Ge2Sb2Te5-based materials appears in Ge 1.8 In 0.2 Sb2Te5 material, its value is 0.35W m -1 K -1 (ACS Applied Materials & Interfaces, 2019, 11<37): 34046-34052.); The lowest lattice thermal conductivity of GeSb4Te7-based materials reported is in GeSb3BiTe7, which is 0.18 W m -1 K -1 (AppliedPhysics Letters,2022,121:213902.)), Ge 1-x In x The lattice thermal conductivity of Sb4Te7 (x = 0.05) material at 400K is 0.038 W m -1 K -1 ), and has the lowest lattice thermal conductivity among the reported Ge-Sb-Te based materials.

[0118] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the claims attached to the present invention.

Claims

1. A layered thermoelectric material with low lattice thermal conductivity, characterized in that: The structural formula of the thermoelectric material is Ge 1- x In x For Sb4Te7, x is 0<x≤0.

1.

2. The layered thermoelectric material with low lattice thermal conductivity according to claim 1, characterized in that: The x is 0.05, and the structural formula of the thermoelectric material is Ge 0.95 In 0.05 Sb4Te7.

3. A method for preparing a thermoelectric material, characterized in that: For preparing the layered thermoelectric material with low lattice thermal conductivity as claimed in claim 1 or 2, the method comprises the steps of: Step S1, vacuum-packing germanium powder, indium powder, antimony powder and tellurium powder in a quartz tube, heating from room temperature to 950° C., and keeping the temperature at 950° C. for 12<2 hours. After the insulation is completed, quenching the quartz tube; Step S2, heating the quartz tube from room temperature to 590°C < 5°C at a heating rate of 2-5°C / min, and keeping it at this temperature for 40-55h, and then naturally cooling it to room temperature; Step S3, grinding and sieving the material obtained in step S2, and then hot pressing and sintering it into a dense block. The hot pressing and sintering temperature is 420°C, the insulation time is 30 minutes, and the pressure is 50MPa. After the sintering is completed, a single-phase thermoelectric material is obtained.

4. The method for preparing a thermoelectric material according to claim 3, characterized in that: In the step S1, the purity of the germanium powder, indium powder, antimony powder and tellurium powder is 99.99%.

5. The method for preparing a thermoelectric material according to claim 3, characterized in that: The heating rates in step S1 and step S2 are both 2-5° C. / min.

6. The method for preparing a thermoelectric material according to claim 3, characterized in that: In the step S3, the mesh size of the ground and sieved sieve is 100 meshes.

7. The method for preparing a thermoelectric material according to claim 3, characterized in that: In step S3, the density of the single-phase thermoelectric material prepared by hot pressing and sintering is 6.34-6.44 g / cm 3 .